Variants of unknown significance in fetal heart malformations: distribution and impact on prenatal decision-making - Wang, Qingsong; Yin, Jun; Zhang, Xiaomeng; Ou, Huimin; Li, Fuyan; Zhang, Yundong; Guo, Caiyu; Wan, Weiyi; Cao, Yongyu; Luo, Tongyong; Wang, Xianmin (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the distribution patterns of variants of unknown significance (VUS) in fetuses with heart malformations (CHD) combined with extracardiac abnormalities and their impact on prenatal decision-making.MethodsA retrospective analysis was conducted on the chromosomal microarray analysis (CMA) data of 697 cases of fetal heart malformations (including simple, complex, and combined with extracardiac abnormalities) and 2,689 controls from Sichuan Provincial Maternal and Child Health Care Hospital between January 2020 and August 2022. Copy number variants (CNVs) were classified according to the ACMG guidelines (pathogenic, VUS, benign), and the differences in VUS detection rates and their impact on pregnancy outcomes were compared among groups.ResultsAmong 697 fetuses with prenatally diagnosed cardiac malformations, 602 (86.37%) had simple, 69 (9.90%) complex, 18 (2.58%) combined with structural extracardiac anomalies, and 8 (1.15%) with soft markers. Karyotype abnormalities occurred in 4.74% (26/549), 16.36% (9/55), 27.78% (5/18), and 12.50% (1/8) of these groups, respectively, all exceeding controls (4.71%, P < 0.05). Pathogenic CNVs were detected in 4.88% (27/553), 7.69% (5/65), 8.33% (2/24), and 0% (0/2), respectively; the first three rates were significantly higher than controls (1.38%, P < 0.05, P = 0.002, P = 0.033). VUS rates rose progressively: 0.54% (3/553), 1.54% (1/65), 12.50% (3/24), and 100% (2/2). Among nine VUS-positive pregnancies, six resulted in live-born infants without abnormalities; three were terminated due to additional malformations or parental anxiety.ConclusionFetuses with cardiac malformations accompanied by structural extracardiac anomalies carry the highest genetic risk; karyotyping combined with CMA should therefore be performed routinely. Complex cardiac malformations also warrant concurrent testing, whereas simple malformations and those with soft markers can be evaluated individually.